Human Resource Management – Eine Annäherung in kritischer Absicht; Human Resource Management – Towards a Critical Perspective - Hartmut Wächter (Industrielle Beziehungen, 2013)
Human Resource Management (HRM) ist trotz umfangreicher Diskussion in der amerikanischen, britischen und deutschsprachigen Literatur ein schillernder Begriff geblieben, mit dem unterschiedliche Phänomene und Konzepte verbunden werden. Auch Versuche, den ökonomischen Erfolg des HRM messbar zu machen, haben zu keinen schlüssigen Ergebnissen geführt. Die Kritik ist aus diesem Grund und aus grundsätzlichen konzeptionellen Erwägungen beträchtlich. Die HRM-Literatur könnte durch stärkere Einbeziehung der Industrial-Relations-Literatur an Realitätsgehalt gewinnen. Dies gilt besonders für die deutschsprachige Literatur. – – Despite the extensive discussion of Human Resource Management (HRM) in the American, British and German literature, this concept has remained a “floating signifier” (Keenoy). A wide variety of phenomena and concepts are associated with HRM. Moreover, attempts to measure the economic effects of HRM have yet to produce any conclusive results. For this reason and due to conceptual ambiguities, criticism of HRM has been substantial. If more attention were paid to the literature on industrial relations, the HRM literature could acquire a greater sense of realism. This is especially true for the literature in German-speaking countries.
Keywords: B10; J50; J53; L21; M12; M54; 330; human resource management; comparative analysis; critical management studies; industrial relations